"Debt on Me Head": A Qualitative Study of the Experience of Teenage Cannabis Users in Treatment. Issue 3 (July 2019) - James, Philip David; Comiskey, Catherine; Smyth, Bobby P.
Abstract: Background: Cannabis is the most commonly used illicit drug in most western countries. In Ireland, it now accounts for most new presentations to substance use treatment services. Cannabis use for most of these people commenced during adolescence. Although a significant amount of research has been conducted on the effects of cannabis on physical and mental health, less is known about the experiences of young cannabis users. Objective: The aim of this study was to understand more about the experience of young, treatment-seeking, cannabis users. Methods: This descriptive qualitative study interviewed eight adolescents who were attending outpatient treatment services for cannabis misuse in Dublin, Ireland. Data were analyzed using thematic analysis. Results: Six themes were identified incorporating the early onset of cannabis and heavy use, involvement in criminality including drug dealing to pay for cannabis, ambivalence, experience of treatment, and damage to relationships. These themes are discussed in light of emerging literature. Conclusion: Young cannabis users in treatment can clearly identify many negative aspects of their cannabis use but are particularly ambivalent toward cannabis. Reluctance to aim for abstinence is common.